2000
DOI: 10.1677/joe.0.1650115
|View full text |Cite
|
Sign up to set email alerts
|

The effect of epidermal growth factor and IGF-I infusion on hepatic and renal expression of the IGF-system in adult female rats

Abstract: Systemic administration of epidermal growth factor (EGF) in neonatal rats results in reduced body weight gain and decreased circulating levels of IGF-I, suggesting its involvement in EGF-induced growth retardation.We investigated the effect of EGF and/or IGF-I administration for 7 days on circulating IGF-I and IGFBP levels and hepatic and renal IGF-system mRNA expression profiles in adult female rats. EGF administration (30 µg/rat/day) did not influence body weight, liver or kidney weight. In contrast, IGF-I (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
2
8
1
Order By: Relevance
“…As discussed, downregulation of IGFBPs can occur at the transcriptional level or at the post-translational level (Vinter-Jensen et al 1996, Edmondson et al 1999, van Neck et al 2000, Ozawa et al 2004. Our data demonstrating reduced IGFBP-3 and -4 mRNA levels support a transcriptional regulatory mechanism.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…As discussed, downregulation of IGFBPs can occur at the transcriptional level or at the post-translational level (Vinter-Jensen et al 1996, Edmondson et al 1999, van Neck et al 2000, Ozawa et al 2004. Our data demonstrating reduced IGFBP-3 and -4 mRNA levels support a transcriptional regulatory mechanism.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, administration of EGF to neonatal rats resulted in reduced body weight, decreased circulating IGF-I, and increased serum IGFBP-1 levels (Murray et al 1993, van Neck et al 2000. However, EGF administration to adult female rats did not result in a reduction of growth (van Neck et al 2000). Our data demonstrates that a second EGFR ligand, HB-EGF, retards growth early in development through an IGF-related pathway.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…It is known that IGF-I is a stimulant of IGFBP synthesis in rat liver [26]. Our result showed the increase of hepatic IGF-I and IGF-II expressions in HP-UN and BCAA-UN, so that the elevated IGFBPs in fetal liver might be the result of an increased IGF expression.…”
Section: Discussionsupporting
confidence: 49%
“…Scharf et al (1996) reported that IGF-I is a potent stimulator for the synthesis of IGFBP-3 and ALS, in co-cultures of Kupffer cells and hepatocytes in adult rats, and that GH did not exert direct effects on IGFBP-3 synthesis, but stimulated the expression of ALS. In adult female rats, serum IGFBP-3 as well as hepatic IGFBP-3 mRNA levels increased after IGF-I treatment (van Neck et al 2000). In contrast, IGF-I mRNA levels and IGFBP-3 mRNA in the liver were reduced in hypophysectomized rats, and GH treatment increased both of them (Domene et al 1993).…”
Section: Discussionmentioning
confidence: 91%